Dual role of neddylation in transcription of hepatitis B virus RNAs from cccDNA and production of viral surface antigen - Qu, Bingqian; Nebioglu, Firat; Leuthold, Mila; Ni, Yi; Mutz, Pascal; Beneke, Jürgen; Erfle, Holger; Vondran, Florian W. R.; Bartenschlager, Ralf; Urban, Stephan (JHEP reports, 2022)
HBV persistence is maintained by both an episomal covalently closed circular (ccc)DNA reservoir and genomic integration of HBV DNA fragments. While cccDNA transcription is regulated by Cullin4A-DDB1-HBx-mediated degradation of the SMC5/6 complex, HBsAg expression from integrants is largely SMC5/6 independent. Inhibiting neddylation of Cullin-RING ubiquitin ligases impairs degradation of substrates. Herein, we show that targeting neddylation pathway components by small-interfering (si)RNAs or the drug MLN4924 (pevonedistat) suppresses expression of HBV proteins from both cccDNA and integrants.